Retrospective analysis of negative cytology results correlated with a positive high-risk in the human papillomavirus result and subsequent results of patients over a period of three years - Piotrowski, Paweł Gerard; Jeleń, Michał Teodor (Polish Journal of Pathology, 2024)
This research paper evaluates the efficacy of co-testing in precluding cervical cancer, with a particular focus on distinguishable outcomes of the human papillomavirus (HPV) vs. cytology tests. A retrospective review of 5948 patients, who tested positive for high-risk HPV but showed negative cytologic findings, revealed that 15.006% tested positive in subsequent screenings. A comparative analysis of various commercial HPV tests highlighted the precision of mRNA-based HPV testing by Aptima (Hologic) in reducing the likelihood of false-negative cytology. The paper challenges the conviction that a negative cytology alone suffices advocating for a condensed testing interval in instances of positive HPV outcomes, thereby facilitating earlier intervention and optimal preventive care. These findings unveil an exigency for reconsidering preventive strategies based on test outcomes.